Prevalence, faecal shedding and genetic characterisation of Yersinia spp. in sheep across four states of Australia. Issue 5 (May 2016) - Yang, R; Ryan, U; Gardner, G; Carmichael, I; Campbell, AJD; Jacobson, C
Abstract : Objectives: To develop molecular tools for the investigation of the prevalence, species and faecal shedding of Yersinia in sheep. Methods: A quantitative PCR (qPCR) targeting the β subunit of the Yersinia spp. RNA polymerase gene was developed and validated. The prevalence of pathogenic Y. enterocolitica was determined by screening for the virulent yst gene. These qPCR assays were used to determine Yersinia spp. prevalence and faecal shedding concentration from 3412 faecal samples collected from approximately 1189 lambs (100–180 lambs/flock) on eight farms across Australia. This was a longitudinal study, with sheep sampled on three occasions (weaning, post‐weaning and pre‐slaughter). A subset of up to five positive samples from each sampling on each farm (n = 111) was sequenced. Results: Yersinia spp. (including both pathogenic and non‐pathogenic species) were identified in all flocks, with 60.7% of lambs shedding Yersinia spp. on at least one sampling occasion. Point prevalence ranged from 4% to 91% across farms and sampling occasions. Median Yersinia spp. bacterial concentration was 1.1 × 10 6, 2.8 × 10 6 and 5.6 × 10 5 organisms/g faeces at weaning, post‐weaning and pre‐slaughter, respectively, across all farms. Pathogenic Y. enterocolitica was identified in all eight flocks sampled, with 14.8% of lambs shedding pathogenic Y. enterocolitica on at least one sampling occasion . Conclusion: Yersinia spp. and pathogenic Y. enterocolitica in particular were commonly identified in a sample of Australian sheep flocks using molecular techniques. Further studies into associations between faecal shedding of pathogenic Yersinia spp. and sheep productivity or clinical disease may utilise qPCR in conjunction with other diagnostic tools.